Effect of NH2-terminal acetylation on the oxygenation properties of vertebrate haemoglobin. Issue 19 (12th October 2020) - Natarajan, Chandrasekhar; Signore, Anthony V.; Kumar, Vikas; Weber, Roy E.; Fago, Angela; Storz, Jay F.
Abstract : In vertebrate haemoglobin (Hb), the NH2 -terminal residues of the α- and β-chain subunits are thought to play an important role in the allosteric binding of protons (Bohr effect), CO2 (as carbamino derivatives), chloride ions, and organic phosphates. Accordingly, acetylation of the α- and/or β-chain NH2 -termini may have significant effects on the oxygenation properties of Hb. Here we investigate the effect of NH2 -terminal acetylation by using a newly developed expression plasmid system that enables us to compare recombinantly expressed Hbs that are structurally identical except for the presence or absence of NH2 -terminal acetyl groups. Experiments with native and recombinant Hbs of representative vertebrates reveal that NH2 -terminal acetylation does not impair the Bohr effect, nor does it significantly diminish responsiveness to allosteric cofactors, such as chloride ions or organic phosphates. These results suggest that observed variation in the oxygenation properties of vertebrate Hbs is principally explained by amino acid divergence in the constituent globin chains rather than post-translational modifications of the globin chain NH2 -termini.